A preliminary analysis of the association between perceived stigma and HIV-related pain in South Africans living with HIV - Wadley, A. L., T. , M.,Pincus, Evangeli (My University, 2019)
Stigma related to the human immunodeficiency virus (HIV) remains common and has been associated with severity of HIV-related symptoms. Associations between HIV stigma and HIV-related pain, one of the most common symptoms in HIV, have however not been investigated. Data from low back pain populations suggest that stigma is associated with worse pain intensity and so we hypothesised that the same would be the case in HIV.
Article submitted to the Faculty of Health Sciences Library, University of the Witwatersrand, Johannesburg. 13 -02-2019